Identidad personal, nacional y universal (1996)
In the first section, personal identity is analysed as a type of qualitative, - not individual identity, íncludíng a reference to one's conceptíon of life, This leads to a concept of happiness as concem for one's future. In the second section the question is raised whether in modemity the conceptíon of one's identity can be satisfactory only if it ís moral, that is universalistic, and whether it can also be particularistic (national). The first question is left open, but it is maintained that universalism does not exelude particularism. Finally, pathological forms of modem identity are brieflv sketched: worth mentíoning is the attitude of indifference towards the peor, who are unable to even pose the question of identity.